Overview of antidiabetic drug use in type-2 diabetes mellitus patients in the outpatient installation of the Islamic University of Indonesia Hospital: Gambaran penggunaan obat antidiabetika pada pasien diabetes melitus tipe-2 di instalasi rawat jalan Rumah Sakit Universitas Islam Indonesia - Fajrin R., Muhammad Galih; Wahid, Rahmat A Hi (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2025)
Diabetes mellitus (DM) is a chronic disease that occurs when the pancreas does not produce enough insulin or the body does not use the insulin that is made efficiently. The prevalence of DM in Indonesia has increased from 6.9% in 2013 to 8.5% in 2018. Meanwhile, in the Special Region of Yogyakarta in 2021 there were 83,568 patients, and Bantul Regency had 15,727 DM patients. This study aimed to describe the use of antidiabetic drugs in outpatient type 2 DM patients at the UII Hospital, Yogyakarta from January to June 2023. This research method is non-experimental research. Data collection was retrospective by taking medical record data of outpatients from January to June 2023. Sampling using purposive sampling method so that 92 samples were obtained. The results obtained antidiabetic drugs most commonly used in combination therapy are metformin and glimepiride as many as 25 cases (60%) and in single therapy the most commonly used drug is metformin with 22 cases (44%). The study concluded that antidiabetic therapy used at the UII Hospital, Yogyakarta was sulfonylurea and biguanid groups as many as 25 cases (60%) in combination therapy and sulfonylurea groups as many as 22 cases (44%) in single therapy.